2016
DOI: 10.1158/1078-0432.ccr-15-0297
|View full text |Cite
|
Sign up to set email alerts
|

Circulating DNA as a Strong Multimarker Prognostic Tool for Metastatic Colorectal Cancer Patient Management Care

Abstract: Purpose: Circulating cell-free DNA (ccfDNA) is a valuable source of tumor material obtained from a simple blood sampling that enables noninvasive analysis of the tumor genome. Our goal was to carry out a multiparametric analysis of ccfDNA and evaluate its prognostic value by investigating the overall survival (OS) of 97 metastatic colorectal cancer patients (mCRC).Experimental Design: Qualitative parameters (determination of the main KRAS exon2 and BRAF V600E mutations) and quantitative parameters (total ccfDN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 41 publications
5
108
0
2
Order By: Relevance
“…However, technological shortcomings and difficulty in finding the perfect markers to identify such CTCs or ctDNA have resulted in few studies of any clinically valuable difference in terms of survival outcomes or prediction[31]. Other studies appear promising, including one recent meta-analysis on the prognostic role of ctDNA[32], also for disease prediction but are small and need further validation[33-35]. …”
Section: Liquid Biopsies: Circulating Tumor Cells and Circulating Tummentioning
confidence: 99%
“…However, technological shortcomings and difficulty in finding the perfect markers to identify such CTCs or ctDNA have resulted in few studies of any clinically valuable difference in terms of survival outcomes or prediction[31]. Other studies appear promising, including one recent meta-analysis on the prognostic role of ctDNA[32], also for disease prediction but are small and need further validation[33-35]. …”
Section: Liquid Biopsies: Circulating Tumor Cells and Circulating Tummentioning
confidence: 99%
“…Qualitative characteristics, such as methylated cfDNA levels have also been shown to independently predict OS in mCRC[62]. In the largest published prospective mCRC patient cohort ( n = 97), El Messaoudi et al[63] used qPCR and showed that cfDNA levels, higher specific mutation loads and the level of cfDNA fragmentation are strong prognostic factors; cfDNA levels were independent prognostic factors for the entire patient cohort and the level of fragmentation only for the KRAS/BRAF mutated subset. Specifically, a difference in OS of 10 mo was reported between the groups of high vs low cfDNA levels (18.07 mo vs 28.5 mo respectively, P = 0.0087)[63].…”
Section: Cell-free Dna As a Prognostic Markermentioning
confidence: 99%
“…In the largest published prospective mCRC patient cohort ( n = 97), El Messaoudi et al[63] used qPCR and showed that cfDNA levels, higher specific mutation loads and the level of cfDNA fragmentation are strong prognostic factors; cfDNA levels were independent prognostic factors for the entire patient cohort and the level of fragmentation only for the KRAS/BRAF mutated subset. Specifically, a difference in OS of 10 mo was reported between the groups of high vs low cfDNA levels (18.07 mo vs 28.5 mo respectively, P = 0.0087)[63]. Finally, Spindler et al[64] compared the prognostic value of the detection of KRAS mutations in the plasma compared to the primary tumor with the use of qPCR, with the former being an independent predictor for OS (HR = 2.98, 95%CI: 1.53-5.80, P = 0.001) and PFS (HR = 2.84, 95%CI: 1.46-5.53, P = 0.002), whereas the latter had no correlation with outcomes, which underscores the value of cfDNA qualitative testing.…”
Section: Cell-free Dna As a Prognostic Markermentioning
confidence: 99%
“…The detection of ctDNA can be used for obtaining diagnostic, prognostic and theranostic information concerning cancer. The diagnostic utility of ctDNA primarily stems from the presence of somatic genomic alterations, such as in the KRAS , BRAF and EGFR genes, which are absent from DNA taken from matched normal cells and in the circulating cell-free DNA (ccfDNA) of healthy subjects [1,2,3,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%